Cabazitaxel plus carboplatin for the treatment of men with metastatic castration-resistant prostate cancers: a randomised, open-label, phase 1–2 trial. Issue 10 (October 2019) - Corn, Paul G; Heath, Elisabeth I; Zurita, Amado; Ramesh, Naveen; Xiao, Lianchun; Sei, Emi; Li-Ning-Tapia, Elsa; Tu, Shi-Ming; Subudhi, Sumit K; Wang, Jennifer; Wang, Xuemei; Efstathiou, Eleni; et al.
Summary: Background: Taxane–platinum combinations have shown promising activity in metastatic castration-resistant prostate cancers in single-group clinical studies but not in randomised trials. Distinct biological subsets of the disease might derive the greatest benefit from the addition of platinum. We aimed to determine whether adding carboplatin to cabazitaxel would improve the outcomes of men with metastatic castration-resistant prostate cancer. Methods: We did a phase 1–2, open label, randomised study at two centres in men with progressive metastatic castration-resistant prostate cancer. In phase 1, patients received intravenous cabazitaxel 20–25 mg/m 2 and intravenous carboplatin area under the curve (AUC) 3–4 mg/mL per min every 21 days. The maximum tolerated dose was defined as the highest dose cohort studied in which one of six or fewer patients experienced a dose-limiting toxicity. In phase 2, patients were randomly assigned (1:1) centrally by a computerised algorithm to intravenous cabazitaxel 25 mg/m 2 with or without intravenous carboplatin AUC 4 mg/mL per min. All patients received growth factor support and oral prednisone 10 mg daily. The primary endpoints were the maximum tolerated dose of the combination in phase 1 and investigator-assessed progression-free survival in phase 2. This trial is registered at ClinicalTrials.gov, number NCT01505868 . Findings: Between Aug 17, 2012, and May 11, 2015, nine patients completed phase 1 as planned, and 160 were randomly assigned to cabazitaxel (n=79) or cabazitaxel plus carboplatin (n=81) in phase 2. During phase I, grade 3 adverse events were anaemia (n=2), fatigue (n=1), thrombocytopenia (n=1), hypomagnesaemia (n=1), diarrhoea (n=1), hypokalaemia (n=1), anorexia (n=1), and dehydration (n=1), and no grade 4 adverse events occurred. No dose-limiting toxicities were observed, therefore, a maximum tolerated dose of cabazitaxel of 25 mg/m 2 and carboplatin of AUC 4 mg/mL per min was selected for phase 2. At a median follow-up of 31·0 months (IQR 20·5–37·1), the combination improved the median progression-free survival from 4·5 months (95% CI 3·5–5·7) to 7·3 months (95% CI 5·5–8·2; hazard ratio 0·69, 95% CI 0·50–0·95, p=0·018). In the phase 2 study, the most common grade 3–5 adverse events were fatigue (7 [9%] of 79 in the cabazitaxel group vs 16 [20%] of 81 in the combination group), anaemia (3 [4%] vs 19 [23%]), neutropenia (3 [4%] vs 13 [16%]), and thrombocytopenia (1 [1%] vs 11 [14%]). There were no treatment-related deaths. Interpretation: Carboplatin added to cabazitaxel showed improved clinical efficacy compared with cabazitaxel alone for men with metastatic castration-resistant prostate cancer. Although adverse events were more common with the combination, the treatment was safe and generally well tolerated. Our data suggest that taxane–platinum combinations have a clinically beneficial role in advanced prostate cancer and a randomised phase 3 study is planned. Funding: Sanofi Genzyme, University of Texas MD Anderson Cancer Center Prostate Cancer Moon Shot Program, Solon Scott III Prostate Cancer Research Fund, National Institutes of Health, and National Cancer Institute.